Estudo de caso sobre o regime próprio de previdência social do estado do Ceará: contexto, modelagem e reformas - Aguiar, Talvani Rabelo (2017)
This study analyzes the solvency of the social security system in Ceará State after the "separation of masses" from public civil servants and the creation of a specific social security fund for military servants. The deficit social security funds were analyzed individually and on consolidated basis, since the State makes financial contributions to honor the payment of retirement and pension benefits. The study used the econometric model fiscal reaction function to evaluate the sustainability of public pensions “cearense” between 2004-2016, based on bimonthly data collected from the Summarized Budget Execution Reports and from the State accounting system. The results, according to the model, point to the insolvency of the pension fund of civil servants, solvency of the fund of the military servants and in the aggregate, insolvency of the social security debt of the State of Ceará.